Silver incorporated microencapsulation of n-hexadecane and n-octadecane appropriate for dynamic thermal management in textiles - Önder, Emel; Ukuşer, Gökçen; SARIER, NİHAL (Elsevıer Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlandi, 2015)
This study concerns with interfacial in-situ encapsulation of n-hexadecane and n-octadecane cores in poly(urea-formaldehyde) shells to fabricate microcapsules, capable of absorbing and releasing high amounts of heat consistently. The microcapsules were designed to show improved thermal properties with drastically reduced particle sizes and included silver nanoparticles (Ag NPs). Using high stirring rates in preparation and polymerization processes resulted in particle sizes ranging in between 163 and 496 nm on average. The encapsulation method was also improved by adding freshly produced silver nanoparticles (Ag NPs) into the in-situ polymerization processes, via the Tollen's reaction, to investigate their contribution to the thermal properties of some types of microcapsules. Phase change enthalpies of the microcapsules produced with n-hexadecane core were obtained as 137 J g(-1) at 22-26 degrees C and the microcapsules produced with n-octadecane core were obtained as 168 J g(-1) at 33-35 degrees C even after hundred cycles. Thermal conductivities of the microcapsules including Ag NPs were considerably higher than those of the microcapsules, not treated with silver nanoparticles. Thus, the microcapsules produced in this study were found fairly appropriate for a wide range of industrial applications specifically in the thermally enhanced clothing fabrics, technical textiles such as medical and automobile textiles, and building materials. The encapsulation process has also the potential of large scale production in the manufacture of microcapsules. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: n-Hexadecane; n-Octadecane; Silver; Tollen's reaction; Heat storage